Person-to-person interaction in twenty-first-century society: Technology and arts at the service of communication - de Miguel Álvarez, Laura; Yáñez Martínez, Begoña (International journal of design in society, 2021)
The creative process in Arts shares with design its origins and development in the search for solutions that integrate both message and form. Design is meant to occupy a special place since it draws from the creativity of arts and makes a significant contribution to effective visual communication. Therefore, it can be a factor in fulfilling the needs of a society living in a two-faced reality: physical and digital interaction. Society needs to consider the structure of interaction that goes beyond using technological tools intended for human-computer interaction (HCI). In fact, it refers to the analogue world that encourages person-to-person interaction, even though it happens via digital and/or virtual means. Dealing with Fine Arts in the Mobility and User Experience group of UNIR has opened a new framework allocated to research in the field of design and develop solutions that bind together artistic processes and technological interactivity in order to provide users a meaningful communication. Through Arts, the present study aims to establish a first approach to this relation between arts and technology that applies to the forms of digital communications today.
Keywords: design; society; communication; arts; interactivity; Scopus